Homelessness during COVID-19: challenges, responses, and lessons learned from homeless service providers in Tippecanoe County, Indiana - Natalia M. Rodriguez; Alexa M. Lahey; Justin J. MacNeill; Rebecca G. Martinez; Nina E. Teo; Yumary Ruiz (BMC, 2021)
Abstract Background The COVID-19 pandemic laid bare some of the United States' most devastating health and social inequities faced by people experiencing homelessness. Homeless populations experience disproportionate rates of underlying health conditions, stigma and marginalization that often disenfranchise them from health and social services, and living conditions that potentiate the risk of COVID-19 transmission and adverse outcomes. Methods Guided by the socio-ecological model, this community-based participatory research study examined the impacts of the COVID-19 public health crisis on people experiencing homelessness in Tippecanoe County, Indiana, and the ways in which homeless service providers prepared for, experienced, and responded to the pandemic. Eighteen (18) semi-structured interviews were conducted with representatives of 15 community-based organizations, including shelters and other homeless service providers. Results Qualitative content analysis revealed myriad challenges at the individual and interpersonal levels faced by people experiencing homelessness as a result of the pandemic, and multilevel responses for COVID-19 impact mitigation in this community. Many of the emergency measures put in place by homeless service providers in Tippecanoe County, Indiana created opportunities for innovative solutions to longstanding challenges faced by homeless populations that are informing better service delivery moving forward, even beyond the COVID-19 pandemic. Conclusions Community-based organizations, including homeless shelters, are uniquely qualified to inform pandemic response and disaster risk mitigation in order to respond appropriately to the specific needs of people experiencing homelessness. The lessons learned and shared by homeless service providers on the frontline during the COVID-19 pandemic have important implications to improve future disaster response for homeless and other vulnerable populations.